Employees at work in Sheeting Department at Hercules Hopewell plant - Hercules Incorporated (1957)
General view of two unidentified employees using a machine to cut stock of so-called "chemical cotton" into sheets at the Hercules Powder Company plant in Hopewell, Virginia. Chemical cotton, a type of purified cellulose obtained from raw cotton linters, is commonly used for the manufacture of cellulose ethers, i.e. water-soluble polymers that have a variety of uses as thickeners, binders, and water-retention agents in products ranging from ceramics and paints to food, cosmetics, and pharmaceuticals. Formed in 1912 as part of an anti-trust settlement with DuPont, the Hercules Powder Company (later Hercules Inc.) initially specialized in the manufacture of explosives and smokeless powders and subsequently diversified its business to encompass a variety of industrial products, including pine and paper chemicals, synthetics, pigments, polymers, and cellulose.
Keywords: Employees; Chemical industry; Cotton; Hercules Incorporated; Corporations; Cellulose; Machinery